Genetics of methyl-accepting chemotaxis proteins in Escherichia coli: organization of the tar region. - Slocum, M K (1983)
The tar locus of Escherichia coli specifies one of the major species of methyl-accepting proteins involved in the chemotactic behavior of this organism. The physical and genetic organization of the tar region was investigated with a series of specialized lambda transducing phages and plasmid clones. The tar gene was mapped at the promoter-proximal end of an operon containing five other chemotaxis-related loci. Four of those genes (cheR, cheB, cheY and cheZ) are required for all chemotactic responses; consequently, polar mutations in the tar gene resulted in a generally nonchemotactic phenotype. The fifth gene, tap, was mapped between the tar and cheR loci and specified the production of a 65-kilodalton methyl-accepting protein. Unlike the tar locus, which is required for chemotaxis to aspartate and maltose, mutants lacking only the tap function had no obvious defects in chemotactic ability. Genetic and physical maps of the tar-tap region were constructed with Mu d1 (Apr lac) insertion mutations, whose polar properties conferred a phenotype suitable for deletion mapping studies. Restriction endonuclease analyses of phage and plasmid clones indicated that all of the genetic coding capacity in the tar region is now accounted for.